Evaluation of the Antioxidant Properties of Black Acacia (Acacia mearnsii) Tannin in Vulcanized Natural Rubber Using Different Vulcanization Systems - Filgueira, Matheus da Silva [UNESP]; Pinto, Leandro Ferreira [UNESP]; Hiranobe, Carlos Toshiyuki [UNESP]; de Freitas, Amanda de Sousa Martinez; Rodrigues, Jéssica de Souza [UNESP]; de Oliveira, André Luis; Ferreira, Marystela; Kawall, Samara Araújo [UNESP]; Souza, Dener da Silva [UNESP]; da Silva, Erivaldo Antonio [UNESP]; Nascimento, Eduardo Soares [UNESP]; Silva, Michael Jones da [UNESP]; et al. (My University, 2024)
Given the growing interest of the rubber industry in seeking alternatives that contribute to environmental sustainability, this work aims to present a study of the mechanical, thermal, and structural properties of natural rubber composites using tannin extracted from Acacia mearnsii as an antioxidant agent. Tannin is a natural and biodegradable product, rich in polyphenols and known for its antioxidant properties. The analyses assessed the effectiveness of incorporating tannins (0, 1, 1.5, and 2 parts per hundred rubber) into sulfur-crosslinked natural rubber composites using a binary accelerator system across three distinct vulcanization schemes: conventional, semi-efficient, and efficient. Initially, tannin characterization tests were conducted, revealing characteristic polyphenol bands of proanthocyanidin catechins, a high total phenolic content, and a substantial reduction in antioxidant activity. These findings highlight the significant antioxidant potential of tannins, particularly for industrial and biological applications. The analyses of the characteristics of natural rubber composites with tannin incorporation indicated that the type of vulcanization process directly affects the antioxidant action of the plant tannin, with the tannins being most effective in the efficient system due to the formation of monosulfidic and disulfidic bonds. Furthermore, the incorporation of tannin did not compromise the physical and chemical properties of the materials, highlighting it as a viable additive for the rubber industry.
Keywords: antioxidant; black acacia; photodegradation; tannin; vulcanization systems